Introduction: Postcolonial Reading Publics - Mukherjee, A (Cambridge University Press, 2017)
In this introduction to the special issue, “Postcolonial Reading Publics,” Mukherjee charts the history of reception of two texts, one a Bengali novel published in British India, the other a Shakespeare adaptation staged in twenty-first-century Kolkata, to examine the fortuitous ways in which reading publics baffle or exceed authorial intention and the given text’s addressable objects. Offering summaries of and continuities among the four essays that constitute the volume, the introduction ends with an analysis of the salience of this discursive context for postcolonial writing, theory, and critique in a world literary frame.